(untitled) (Research, Society and Development, 2020)
It analyzes the management of the collection and transport of Urban Solid Waste (MSW) in the city of Castanhal in 2019. The research is of the exploratory descriptive type and was developed in 3 stages. The planning instruments of the MSW sector in the municipality were checked (step 1), the operational aspects of the collection and transport of MSW were analyzed (step 2) and systematized and the operating costs of the collecting vehicles (step 3) were analyzed. The results allowed to identify that the Municipal Plan for Integrated Management of Solid Waste (PMGIRS) was not elaborated and that there were deficiencies in the provision of the service, such as the lack of information on the limits of the sectors, itineraries, routes and times of productive, unproductive and carriage. It was also found that 17 collecting vehicles were unable to operate (80.95% of the fleet) and that 43 of the 119 employees could be relocated to other activities (36.13% of the garrison). The conclusion of the research is that the operational deficiencies contributed to the total cost of the collecting vehicles of R 2,159,985.30 (2019), 211.75% higher than the amount collected with the urban services fee (TSU), contained in the IPTU for the management of the MSW sector (R 692,863.81). There was also a need for technical planning to improve efficiency and reduce costs in providing MSW collection and transportation services in the city of Castanhal.